Computer concepts 2013 : comprehensive - Parsons, June Jamrich; Dan Oja (Australia : Course Technology Cengage Learning, 2013)
Get Synched! Learning happens when students and instructors effectively connect and communicate. NEW PERSPECTIVES ON COMPUTER CONCEPTS 2013, Comprehensive, 15E, International Edition makes it possible. This edition goes beyond the computer basics and covers relevant technical and practical information that matter to students' daily lives.
Orientation -- Computers and digital basics -- Computer hardware -- Software -- Operating systems and file management -- Local area networks -- The internet -- The web and e-mail -- Digital media -- The computer industry: history, careers, and ethics -- Information systems analysis and design -- Databases -- Computer programming.
Includes index.
Keywords: COMPUTERS